Transitions from offline to online labor markets: The relationship between freelancers' prior offline and online work experience - Mareike Seifried (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
An emerging stream of research from various disciplines studies online labor market (OLM) platforms as an alternative way of accomplishing work compared to traditional (offline) labor markets. Although prior work has increased our understanding of how OLM platforms function, we so far know very little about the relationship between what workers have done before entering the platform and the skill content of their online jobs. However, the question of why workers do the jobs they do in an online context and what drives their decision is fundamental to understanding how these markets function and are used by workers. Using data on 4,771 freelancers working on Upwork.com, the world's leading freelancing website, we compare the skill content of their online jobs with their last reported offline prior to platform entry. Based on prior work on occupational mobility (Gathmann & Schönberg, 2010) and human capital investments (Becker, 1962), we hypothesize and find that workers with more valuable skillsets adjust their skill portfolios less while working online, i.e. the distance between their offline and online skill portfolio is lower. We further show that being female, coming from an advanced economy and reporting having current offline employment moderates the relationship between skill value and skill distance.
Keywords: J24; J6; J44; 330; Online labor markets; gig economy; labor mobility; occupational mobility; human capital; task-based approach; digital platforms; knowledge work